Smoking, alcohol consumption, and frailty: A Mendelian randomization study - Lv, Jiannan; Wu, Lianghua; Sun, Sheng; Yu, Huifang; Shen, Zekai; Xu, Jun; Zhu, Jiahao; Chen, Dingwan; Jiang, Minmin (Frontiers in Genetics, 2023)
Background: Tobacco smoking and alcohol consumption have been associated with frailty in observational studies. We sought to examine whether these associations reflect causality using the two-sample Mendelian randomization (MR) design. Methods: We used summary genome-wide association statistics for smoking initiation (N = 2,669,029), alcohol consumption (N = 2,428,851), and the frailty index (FI, N =175,226) in participants of European ancestry. Both univariable and multivariable MR were performed to comprehensively evaluate the independent effects of smoking and alcohol consumption on the FI, accompanied by multiple sensitivity analyses. Results were verified using lifetime smoking and alcohol use disorder. Reverse direction MR was undertaken to assess the potential for reverse causation. Results: Genetic predisposition to smoking initiation was significantly associated with increased FI (univariable MR: β = 0.345; 95% confidence interval [CI] = 0.316 to 0.374; P = 1.36E-113; multivariable MR: β = 0.219; 95% CI = 0.197 to 0.241; P = 2.44E-83). Genetically predicted alcohol consumption showed a suggestive association with the FI (univariable MR: β = -0.090; 95% CI = -0.151 to -0.029; P = 0.003; multivariable MR β = -0.153; 95% CI = -0.212 to -0.094; P = 2.03E-07), with inconsistent results in sensitivity analyses. In complementary analysis, genetic predicted lifetime smoking, but not alcohol use disorder was associated with the FI. There is no convincing evidence for reverse causation. Conclusions: The present MR study supported smoking as a causal risk factor of frailty. Further research is warranted to investigate whether alcohol consumption has a causal role in frailty.